2017
DOI: 10.1055/s-0038-1649280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroencephalogram Neurofeedback Training on Quality of Life in Patients with Traumatic Brain Injury: In Context of Spontaneous Recovery

Abstract: Introduction Quality of life (QOL) is strongly affected following traumatic brain injury (TBI). There is a strong need to explore the use of new developments in neuropsychological rehabilitation such as electroencephalogram (EEG) neurofeedback training (NFT) on QOL in TBI patients. Objective The objective was to study the effect of EEG NFT on QOL in TBI patients in the context of spontaneous recovery. Methodology A sample of 60 TBI patients was assigned to an NFT group (n = 30) and a treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Twenty sessions of EEG-NFT were effective in reducing the postconcussive symptoms, perceived stress, and overall levels of dysfunctions (Bennett et al, 2017;Reddy et al, 2014). It was also found that EEG-NFT was equally effective in bringing about these changes regardless of the time since injury (Bennett et al, 2017). Memory scores on neuropsychological testing did not show any change, but forgetfulness and orientation were reported to have improved on the VAS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Twenty sessions of EEG-NFT were effective in reducing the postconcussive symptoms, perceived stress, and overall levels of dysfunctions (Bennett et al, 2017;Reddy et al, 2014). It was also found that EEG-NFT was equally effective in bringing about these changes regardless of the time since injury (Bennett et al, 2017). Memory scores on neuropsychological testing did not show any change, but forgetfulness and orientation were reported to have improved on the VAS.…”
Section: Discussionmentioning
confidence: 91%
“…Twenty sessions of EEG-NFT, each lasting for 40 min on alternate days with a protocol targeting to increase alpha and decrease theta resulted in significant improvements in a wide range of cognitive functions such as processing speed, attention, executive functions, visuospatial construction, learning, and memory in patients with TBI (Reddy, Rajeswaran, Indira Devi, & Kandavel, 2013). EEG-NFT was also found to be useful in improving subjective symptom reporting, perceived stress, and quality of life (Bennett et al, 2018;Bennett, Sampath, Christopher, Thennarasu, & Rajeswaran, 2017;Reddy, Rajeswaran, Bhagavatula, & Kandavel, 2014). These findings suggest that EEG-NFT can lead to dual benefit (i.e., by bringing about improvement in cognitive functions as well as in emotional-behavioral functioning).…”
Section: Eeg-neurofeedback Training (Eeg-nftmentioning
confidence: 99%
“…Also, based on operant conditioning, neurofeedback training (NFT) reinforces desirable self-regulated changes in brain activity and physiological functioning; these changes correspond with improved self-regulation 29–34. NFT showed potential in reducing neurobehavioral symptoms and improved QOL measures 35,36. The study design included 6 quasi-experimental studies14,37–41 and seven 2-group experimental studies, of which 3 are RCTs 12,35,36,42–45…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34] NFT showed potential in reducing neurobehavioral symptoms and improved QOL measures. 35,36 The study design included 6 quasiexperimental studies 14,[37][38][39][40][41] and seven 2-group experimental studies, of which 3 are RCTs. 12,35,36,[42][43][44][45] Among these studies, Brown et al 38 reported significant improvements in depression, anxiety, and PTSD, with differences noted in pre/posttreatment quantitative electroencephalogram (EEG) measures.…”
Section: Biofeedback and Neurofeedbackmentioning
confidence: 99%
See 1 more Smart Citation